Nursing dependency in registered nursing homes and long term care geriatric wards in Edinburgh. Issue 6537 (28th June 1986) - Capewell, A E; Primrose, W R; MacIntyre, C
Abstract : There has been growing interest and public investment in registered nursing homes, apparently based on the assumption that these homes are the private equivalent of hospital long term care. We have tested this hypothesis in a survey comparing 400 patients in 18 registered nursing homes with 217 patients in 11 geriatric long term care wards in Edinburgh. The nursing home patients formed a distinct and separate group: 362 (92%) were women, 392 (98%) were single or widowed, and 358 (90%) were self financing, whereas in the geriatric long term care group 148 (68%) were women and 35 (16%) were still married. Patients in nursing homes were also far less dependent than those in geriatric long term care wards (p less than 0.005). This study suggests that there may be large differences between the patients in these two types of institution, particularly with regard to nursing dependency. This finding has important implications in the future planning of long term places for the dependent elderly.